Lessons from Xi Jinping's Strategic Leadership in Supporting Maritime Policy in the South China Sea - Agustin, Mayang; Soemantri, Asep Iwa; Prakoso, Lukman Yudho; Suwarno, Panji; Pradana, Dimas Gading Arya; Snekubu, Elyakim; Chalizt, Ismaya Kenza; Toelihere, Ivan Fillbert (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
This study analyzes Xi Jinping's maritime policy in the South China Sea with a focus on military power, economic diplomacy, and international law. Xi Jinping uses a militarization strategy through the construction of artificial islands and military infrastructure to strengthen China's territorial claims. In addition, the Belt and Road initiative expands maritime influence through economic cooperation, creating strategic dependencies. This study uses a literature review to compare Xi's maritime policy with previous approaches, and examines its impact on regional tensions, especially with ASEAN countries that have similar claims.